2021
DOI: 10.3390/educsci11070326
|View full text |Cite
|
Sign up to set email alerts
|

Technological Skills in Higher Education—Different Needs and Different Uses

Abstract: Technological skills development is a central issue for a country’s educational and social policies. Throughout their school career, from primary to secondary education and later in higher education, students have the opportunity to build and develop various skills, including technological. Considering the different needs and different uses that these skills encompass, these will certainly be necessary and useful in students’ academic and professional life. This study reports on an investigation of technologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…Moreover, they consider these materials as an essential part of the didactic action, although the opinion about whether they increase student motivation or performance is divided. This result is common to other studies [3,6,10,[12][13][14]25,26]. In general, university teachers feel prepared for the irruption of the digital era in higher education in terms of their own digital and digital-teaching competencies [16], but also as trainers of students who have to develop professional digital competencies in the different fields of working life [27,28].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, they consider these materials as an essential part of the didactic action, although the opinion about whether they increase student motivation or performance is divided. This result is common to other studies [3,6,10,[12][13][14]25,26]. In general, university teachers feel prepared for the irruption of the digital era in higher education in terms of their own digital and digital-teaching competencies [16], but also as trainers of students who have to develop professional digital competencies in the different fields of working life [27,28].…”
Section: Discussionsupporting
confidence: 71%
“…In the context of university education, teachers are expected to evolve rapidly in the technological world, as higher education institutions play a crucial role in developing the digital competence of tomorrow's professionally active citizens [6]. However, the effectiveness of this development can only be assessed by evaluating the teachers' perception of the use of DCC tools and the teaching results obtained in the classroom on concrete actions [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worth mentioning that the recognition of the importance of technology as a tool in education is still insufficient. There is a balance that needs to be met with regard to students' use of technology and other aspects of their life [75]. Weinhandl et al found that teachers who were capable of using technology in teaching were effective as schooling facilitators and that their students who regularly used technology in face-to-face settings effortlessly transitioned to home schooling with the same technology [76].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the two rankings do not differ significantly, but it was suggested that the DESI dimensional structure should be simplified and reconsidered. According to Folea [71], Fleaca [17] and Condruz-Bacescu [72] in the EU Digital Agenda measures to support digital skills education play a crucial role in developing the digital skills of the population, and all Member States have a duty to increase the number of people with basic and higher digital skills [73][74][75]. However, education alone is not enough, as technology must be within reach to ensure that the knowledge acquired can be applied and further developed [76,77].…”
Section: Discussionmentioning
confidence: 99%